The difficulties e-learners face when learning virtually - Menezes, Helena (2011)
This paper tries to give the theoretical framework of e-learning with its advantages and disadvantages. It presents the results of several on-line Portuguese courses. The comparison of those different courses will give insights of the problems e-learners face as well as the benefits found. To contextualize these issues a Virtual Learning Centre (to support teachers) will be presented in order to put in evidence its potentialities and its value as a «training tool».